Team-based Learning (TBL) Module for Vertebral Column Anatomy - William Brooks; David Resuehr; Steven Zehren (Association of American Medical Colleges, 2014)
Abstract Introduction This team-based learning (TBL) module is designed to teach students the clinical gross anatomy of the vertebral column. Specifically, the resource provides learners with information on the presentation, diagnosis, and treatment of a lumbar intervertebral disc herniation. Methods This module utilizes the standard TBL format. Students are assigned a relevant reading assignment from a text as appropriate, along with the learning objectives to focus their preparations prior to the class session. At the beginning of the session, students are divided into teams of five to six persons. A 10-item individual readiness assurance test is then given to each student. Immediately following this, student teams take the group readiness assurance test, which consists of the same 10-question quiz. Following the readiness assurance portion, student teams are given the application exercise, which consists of a clinical case study followed by six multiple-choice questions. Results This TBL module was originally delivered to first-year medical students at the University of Alabama at Birmingham (UAB) in the fall of 2013 in the Fundamentals-I course. The UAB medical class had an enrollment of 192 students. Student evaluation data from the Fundamentals-I module were generally positive regarding the use of TBL in anatomy education. Forty-three percent of students agreed or strongly agreed that TBL was a useful activity, while 30% disagreed and 27% were neutral. Student comments indicated that the TBL activities were helpful in critical thinking regarding the content. Discussion This TBL module is designed to teach students the clinical gross anatomy of the vertebral column and provide a clinical case-based exercise for the application of this knowledge. The content included in this module is suited for a variety of health science disciplines, including medicine, dentistry, optometry, and both physical and occupational therapy.